SPAG5 as a prognostic biomarker and chemotherapy sensitivity predictor in breast cancer: a retrospective, integrated genomic, transcriptomic, and protein analysis - Abdel-Fatah, Tarek M.A.; Agarwal, Devika; Liu, Dong-Xu; Russell, Roslin; Rueda, Oscar M.; Liu, Karen; Xu, Bing; Moseley, Paul M.; Green, Andrew R.; Pockley, Alan G.; Rees, Robert C.; Caldas, Carlos; et al. (Elsevier, 2016)
Background